FAKTOR PENENTU DALAM PEMBELAJARAN PROGRAM PENGUATAN KAPASITAS KELOMPOK (STUDI KASUS PADA KEBERLANJUTAN PROGRAM PENINGKATAN PENDAPATAN PETANI KECIL DI KABUPATEN SUMEDANG) - Surachman Suwardi (JIP ( Jurnal Industri dan Perkotaan ), 2010)
The objectives of this study were to analyze the influence partially and silmutaneously of pheasants characteristic, innovation nature of group capacity building program, suppporting factors and goverment policy trough learning program for rural income generating (RIGP) on adoption level of pheasant on group capacity building program.